Pengaruh Pendidikan Islam terhadap Peserta Didik - Novira, Nuraeni (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2016)
Education and teaching in Arabic language are â€œTarbiyah waTaâ€™lÄ«mâ€, while Islamic education in Arabic language is â€œTarbiyahIslÄmiyahâ€. Education is an attempt to foster and develop thehuman personality, both spiritual aspects and physical thatoccurs in phases. Thus, the best result which is ended onoptimizing the development or growth, can only be achieved ifeducation occurs gradually to the development and growthobjectives. Education is also an approach method that is inaccordance with human character. Islamic education includesfaith education and charity, because the teaching of Islamcontains fostering personal attitudes and society behavior.Islamic education has three phases, they are tilÄwah (reciting theverse of Allah), tazkiyah (purify the soul) and Taâ€™lÄ«m al-KitÄb waal-Sunnah (to teach the Holy Qurâ€™Än and sunnah of the prophet).Keyword : Pendidikan Islam